Optimization of material design of wrench tool based on Finite Element Method in project-based learning scheme - Yusuf Nurhuda; Syaiful Ma’rub Kurnianto; Nur Fitria Pujo Leksonowati; Ihsan Saputra; Rahman Hakim; Chairul Anam; Ahmad Syafi’i (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
In the world of machinery maintenance, auxiliary equipment is needed that can facilitate work in the field of technology and engineering. Wrench tool are included in the category of hand tools that are often used in the world of maintenance. In the use of wrench tool, there are many problems regarding the design model and strength structure of several types of materials used. In general, wrench tool use Chrome Vanadium Steel (AISI 6150) material. In this study, there is one type of wrench tool that has been modified both in form and function through a project-based learning (PBL) learning scheme. A statistical analysis approach using the finite element method (FEM) was carried out with variations in three types of materials. The types of materials are Chromium-Vanadium Steel (AISI 6150), Chromium-Boron Steel (AISI O1), and ASSAB DF2 Steel. ASSAB DF2 Steel material shows the most optimal mechanical characteristics, in terms of stress value of 10.13 MPa, low displacement of 0.029 mm, a high safety factor, with a value of 68.1, and the longest fatigue life with 3.76 × 10⁵ cycles. Therefore, the combination of the new design and ASSAB DF2 Steel material is considered the most suitable for application to wrench tool that require strength, security, and long-term durability as the most effective solution to improve the structural performance and reliability of wrench tool based on simulation results using SolidWorks software